Mismatch epitope load predicts de novo‐DSA‐free survival in pediatric liver transplantation. (13th March 2022) - Shin, Stephanie; Lee, Margaret; Dente, Elizabeth; Yazigi, Nada; Khan, Khalid M.; Kaufman, Stuart S.; Ahn, Jaeil; Timofeeva, Olga A.; Ekong, Udeme D.
Abstract: Background: Our knowledge of de novo anti‐HLA donor‐specific antibodies ( dn DSA) in liver transplantation continues to be defined. We hypothesized that differences of HLA‐DR/DQ mismatches can improve precision in alloimmune risk categorization and be applied to tailor immunosuppression. Methods: A retrospective chart review of 244 pediatric patients consecutively transplanted at our center between 2003 and 2019 was performed to identify patients tested for dn DSA. Records were queried for: demographics, pre‐transplant diagnosis, biopsy‐proven T‐cell‐mediated rejection (TCMR), radiology proven biliary complications, tacrolimus trough levels, dnDSA characteristics, and HLA typing. The eplet mismatch analyses were performed using HLAMatchmaker ™ 3.1. All statistical analyses were conducted using R software version 3.40. Results: There were 99 dn DSA‐negative patients and 73 dn DSA‐positive patients ( n = 70 against class II and n = 3 against class I and II). ROC analysis identified optimal cutoff of eplet mismatch load for dn DSA and defined risk groups for an alloimmune outcome. Kaplan–Meier curves and log‐rank tests showed high eplet mismatch load was associated with shorter dn DSA‐free survival (log‐rank p = .001). Multivariable Cox regression models showed that tacrolimus coefficient of variation and tacrolimus mean levels were significantly associated with dn DSA‐free survival ( p < .001 and p = .036). Fisher's exact test showed that dn DSA was associated with an increased likelihood of TCMR (OR 14.94; 95% CI 3.65 – 61.19; p < .001). Patients without TCMR were more likely to have dn DSA to HLA‐DQ7 and less likely to have dn DSA to HLA‐DQ2 ( p = .03, p = .080). Conclusions: Mismatched epitope load predicts dn DSA‐free survival in pediatric liver transplant, while dn DSA specificity may determine alloimmune outcome.